Political Resources and Divergent Court Empowerment in China: A Subnational Comparison. (November 2019) - Wang, Juan; Liang, Wenting
The cities of Guiyang and Kunming are known among legal scholars, practitioners, and policy makers for hosting two of China's earliest specialized environmental tribunals, following serious water contamination in the two cities. However, the judicialization of environmental protection appears to be relatively nominal in Kunming and substantial in Guiyang. Why? We contend that, at a critical juncture, different political resources available to local leaders—including their past networks and experiences—led them to implement different strategies to deal with these crises. Under similar conditions, different political resources thus led to divergent outcomes of judicial empowerment. We use process tracing to describe the causal sequence in the adoption and application of policies of judicialization. Whether courts are empowered to operate proactively or conservatively is the result of the strategies of local actors in response to the policy agenda set forth by political leaders and constrained by political leaders' available political resources. This study contributes to existing theories of court empowerment in authoritarian regimes that have largely relied on national-level or socioeconomic factors. Through a controlled subnational comparison in China, this article provides an alternative theory of divergent practices of court empowerment.